2015
DOI: 10.1016/j.neuron.2015.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Substrates of Altered Axonal Growth and Brain Connectivity in a Mouse Model of Schizophrenia

Abstract: Summary 22q11.2 deletion carriers show specific cognitive deficits and ∼30% of them develop schizophrenia. One of the disrupted genes is ZDHHC8, which encodes for a palmitoyltransferase. We show that Zdhhc8-deficient mice have reduced palmitoylation of proteins that regulate axonal growth and branching. Analysis of axonal projections of pyramidal neurons from both Zdhhc8-deficient and Df(16)A+/− mice, which model the 22q11.2 deletion, revealed deficits in axonal growth and terminal arborization, which can be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
150
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(167 citation statements)
references
References 46 publications
(61 reference statements)
16
150
0
1
Order By: Relevance
“…Abnormal neuronal alignments have been reported in neuropsychiatric disorders associated with cognitive impairments, such as schizophrenia (55) and autism (56). Interestingly, defective axonal terminal branching that is similar to the impaired corticocortical axonal branching observed in our study has recently been demonstrated in an animal model of schizophrenia (57), lending support to the notion that the impaired corticocortical wiring in brain disorders could cause cognitive impairments.…”
Section: Discussionsupporting
confidence: 89%
“…Abnormal neuronal alignments have been reported in neuropsychiatric disorders associated with cognitive impairments, such as schizophrenia (55) and autism (56). Interestingly, defective axonal terminal branching that is similar to the impaired corticocortical axonal branching observed in our study has recently been demonstrated in an animal model of schizophrenia (57), lending support to the notion that the impaired corticocortical wiring in brain disorders could cause cognitive impairments.…”
Section: Discussionsupporting
confidence: 89%
“…A subsequent study demonstrated that dhhc8-deficient mice showed a decrease in dendritic spine density [239] and disruption of axonal growth [240]. In contrast to the studies described above, several studies have demonstrated no association between dhhc8 gene and susceptibility to schizophrenia [236,[241][242][243][244][245][246].…”
Section: Schizophreniamentioning
confidence: 91%
“…An association between dhhc8 and schizophrenia could be restricted in closely linked genetic locus based on specific ethnic groups or dhhc8 might be indirectly implicated in schizophrenia. In a 22q11.2-deletion mouse model of schizophrenia Df(16)A +/− mice, axonal growth and branching was disrupted in vivo and these deficits were rescued when DHHC8 was exogenously expressed in the mice [240]. In addition, a schizophrenia-related circuit, a prefrontal cortexhippocampus connectivity and spatial working memory were impaired in dhhc8-deficient mice.…”
Section: Schizophreniamentioning
confidence: 99%
“…TBX1 -найбільш вивчений ген у ре-гіоні делеції 22q11.2, гетерозиготи з мутаціями TBX1 мають кардіоваскулярні дефекти, аплазію або гіпо-плазію тимуса та паращитоподібних залоз, гетеро-зиготи за геном DGCR8 -вади розвитку нервової системи. Існують і інші мутації генів LCRs 22q11.2, пов'язані із захворюваннями, щодо більшості яких тривають дослідження на моделях тварин [6,7].…”
Section: îáãîâîðåííÿunclassified